Migration: language policy and linguistic integration - Ina Ferbežar; Matej Klemen (Slovenščina 2.0: Empirične, aplikativne in interdisciplinarne raziskave, 2024)
Our times have been marked by increasingly intensive human migrations. Linguistic communities are now composed of increasingly diverse groups of plurilingual individuals, and this diversity is on the rise with the arrival of new individuals. This has resulted in radical changes in communication practices, and it has been accompanied by rapid developments in language resources and technologies, and services they make possible. All of these factors give rise to major challenges for modern societies, not least among them the linguistic and other types of integration of immigrants into their new community. Such integration is usually linked to the “porosity” of that community – among other things, to the expectations of the community’s majority population and to political decisions, each of which is driven by ideologies of one kind or another.